Grain boundary engineering approaches for the structure optimization in commercial copper M1 - Kozlova, T. V.; Kuznetsov, P. V.; Meisner, S. N.; Burlachenko, A. G.; Mishin, I. P. (Russian physics journal, 2025)
The effect of successive thermomechanical treatment in the strain annealing and strain recrystallization modes to the structure optimization of commercial copper M1 is studied within the grain boundary engineering approach. The chosen thermomechanical treatment modes lead to a significant increase in the twin boundary proportion compared to the recrystallized state, the twin clusters formation, and the disruption of the connectivity of random high-angle boundaries. After the thermomechanical treatment in the strain annealing and strain recrystallization modes, the twin cluster growth has been observed; however, the deviation from the ideal twin misorientation has also been increased.